PP4463-Proposal-for-a-Post-Catastrophe-Debt-Relief-Trust-Fund. (Policy Papers; Policy Paper ;, 2010)
The global crisis has underscored the need for effective global financial safety nets to protect countries with sound policy frameworks from adverse outcomes. Complementing the traditional crisis resolution role of the IMF, which has been instrumental during the recent crisis and is expected to remain dominant going forward, further strengthening instruments to prevent crises and mitigate contagion in systemic events would contribute to the IMF's mandate to secure global stability. This paper proposes specific reforms of crisis prevention instruments, and separately presents further considerations for strengthening the IMF's toolkit for dealing with systemic crises. The proposals, which have benefited from feedback from policymakers and other stakeholders, build on last year's major overhaul of the IMF lending toolkit and the reform options considered earlier this year by the IMF Executive Board in the context of a broader review of the institution's mandate.